Penerapan Metode RUP pada Sistem Informasi Unit Kegiatan Mahasiswa STMIK PalComTech - Andika Widyanto (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
Student Activity Unit (UKM) is a place where students gather who have the same interests and interests in a college. STMIK PalComTech is a private tertiary institution in the city of Palembang which has 5 UKM. When registering prospective SME members, they visited the UKM booths that were opened by the UKM management, besides that there were several other obstacles such as UKM STMIK PalComTech activities recorded manually only from the side PalComTech STMIK Student Affairs, which contains the name of the PIC, date of activity, number, name of UKM, place, start, finish, number of attendance, meetings to, information, there is also data material that is not neatly organized, and monthly report collection. In order to support the recording of activities in terms of attendance, members and material taught up to UKM member registration, the researchers created a web-based SME information system using the Rational Unified Process method and in this study using black box testing. RUP is a method that uses the concept of object oriented, and has activities that focus on the development of the model by using the Unified Modeling Language (UML). The results of this study are an information system that can be used, UKM members, and STMIK PalComTech student affairs that make it easy to collect attendance information, member data, activity data, material and announcements.